Guide the professional development of a newly hired secondary school teacher. A collaborative research in Tuscany. - Giovanna Del Gobbo; Daniela Frison; Luca Salvini; Rossella Bonistalli; Pietro Di Martino; Donatella Fantozzi; Emilio Mariotti; Vera Montalbano; Giovanni Roberi (Firenze University Press, 2023)
The article presents the key dimensions of an intervention research carried out in the framework of a collaboration agreement between the Regional School Office for Tuscany (MI USR) and the universities of Florence, Pisa, and Siena, aimed at the development of tools to support the induction phase, an essential stage for the development of professionalism, of first and second-grade secondary school teachers. The results show the functionality and usefulness of the device from the tutors' point of view.   Orientare lo sviluppo professionale dell'insegnante di scuola secondaria neoassunto. Una ricerca collaborativa in Toscana. Il contributo presenta gli elementi caratterizzanti di una ricerca-intervento realizzata nel quadro di un accordo di collaborazione tra l'Ufficio Scolastico Regionale per la Toscana (MI USR) e gli Atenei di Firenze, Pisa e di Siena, finalizzata alla messa a punto di strumenti a supporto della fase di induction, essenziale per lo sviluppo della professionalità, dei docenti di scuola secondaria di primo e secondo grado. I risultati riguardano la funzionalità e utilità del dispositivo dal punto di vista dei docenti tutor.